Analysis of Criminogenic Factors among Children from Broken Home Families: A Qualitative Study at LPKA Rumbai - Heristiano, Aufa asshidik (Sisi Lain Realita, 2026)
This study aims to analyze criminogenic factors affecting children from broken home families at LPKA Rumbai from a criminological perspective. This research is motivated by the limited number of studies that specifically examine the relationship between broken home conditions and criminogenic factors among juvenile inmates using qualitative analysis supported by software tools. The study employs a qualitative approach through in-depth interviews and document analysis, with data processed using NVivo version 15. The findings indicate that criminogenic factors are influenced by non-intact family conditions, lack of parental attention, limited supervision, and peer environment. These conditions contribute to weakened social control, reflected in low levels of attachment, commitment, involvement, and belief among children. The novelty of this study lies in the use of NVivo to identify patterns of criminogenic factors. The implications highlight the importance of strengthening family roles and optimizing rehabilitation programs in LPKA to prevent deviant behavior among children.